Startup Testing of the PM-2A Nuclear Power Plant - McCool, W. J.; Ryan, R. M.; Richards, W. M. S.; Bradley, P. L.; Stephenson, L. D.; Cox, J. F. (Nuclear Power Engineering Department, Alco Products, Inc., 1962)
Abstract: A detailed description of the PM-2A reactor, primary system and instrumentation is presented. A general description of the secondary system and plant arrangement at Camp Century, Greenland is included. The results of the startup physics, shielding, thermal and hydraulics and radiochemistry test are presented. the analysis performed on the shielding and thermal and hydraulic tests is included. The shielding problem at startup and the shielding modification made to the plant are described along with the radiation measurements made in these areas.